Strategi Branding dan Promosi Produk Aluminium oleh Perajin di Desa Tanjung Atap untuk Mengoptimalkan Pemasaran Produk - Rella Annisa Fitri; Dwi Maharani (Jurnal Aksi Dosen dan Mahasiswa, 2025)
Tanjung Atap Village is one of the central areas of the craftsman industry in Tanjung Batu sub-district, with superior products being aluminum products. The lack of marketing and branding strategy development carried out by aluminum craftsmen in Tanjung Atap Village is a major challenge faced in the increasingly tight local and international market competition. Many craftsmen still use conventional marketing methods which have limited reach, making aluminum products in Tanjung Atap Village less well-known even though the product quality can compete in the market. The Thematic Community Service Lecture activity is aimed at strengthening the capacity of craftsmen in understanding the concept of branding, creating an attractive product identity and utilizing promotional media both online and offline, and increasing product visibility. Branding and promotion activities for aluminum products by craftsmen in Tanjung Atap Village have a significant impact on increasing the competitiveness of local products. Where the training activities for creating Instagram accounts, taking product photos, and making banners were carried out, they succeeded in providing craftsmen with effective promotional tools, both for offline and online marketing and craftsmen now have the tools needed to increase the appeal and reach of their product marketing. Craftsmen who initially did not understand the importance of branding now have a clear brand identity, supported by a logo, brand name, and a targeted promotional strategy, and craftsmen also learn to produce products that are of higher quality and have higher appeal, such as ergonomic and aesthetic designs.